Detection of Modulated Wave Transmission Failure in Aviation Communication Using IoT-Based RTL-SDR - Mukti, Indra Fadillah; Muhammad Arif Sulaiman; Mochamad Faisal Yoga Dewantara (Universitas Muhammadiyah Surakarta, 2024)
Communication is a crucial component in aviation telecommunications services, where failures can lead to fatal incidents that may result in loss of life. According to Regulation No. 48 of 2017, aviation telecommunication service providers must be able to provide VHF A/G services with an availability value of 0.99999 and detect failures within two seconds. At Perum LPPNPI Yogyakarta, the VHF A/G equipment is located in a transmitter building 760 meters away from the Technician Standby Building. This distance makes it difficult for technicians to directly monitor the equipment's condition, leading to failures being identified based on reports from air traffic controllers. Therefore, the author designed an IoT-based RTL-SDR system to directly monitor equipment conditions based on the modulated waves transmitted. This design employs the ADDIE method in its development. The system operates by measuring the transmission power and audio level of the modulated waves. Based on research conducted at frequencies 120.2 MHz, 125 MHz, 126.7 MHz, 127 MHz, 129.5 MHz, 130 MHz, 132.5 MHz, 133.2 MHz, 134 MHz, and 135 MHz, this design can detect equipment failures based on the received modulated waves with highest and lowest deviation while measuring transmission power are 2.24 dB and 0.4 dB.